Added prognostic value of plaque burden to computed tomography angiography and myocardial perfusion imaging. (October 2021) - Ahmed, Ahmed Ibrahim; Han, Yushui; Al Rifai, Mahmoud; Alnabelsi, Talal; Nabi, Faisal; Chang, Su Min; Chamsi-Pasha, Mohammed A.; Nasir, Khurram; Mahmarian, John J.; Cainzos-Achirica, Miguel; Al-Mallah, Mouaz H.
Abstract: Background and aims: Cardiac computed tomographic angiography (CCTA) - derived measures of coronary artery disease (CAD) burden have been shown to independently predict incident cardiovascular events. We aimed to compare the added prognostic value of plaque burden to CCTA anatomic assessment and single photon emission computed tomography (SPECT) physiologic assessment in a cohort with high prevalence of risk factors undergoing both tests. Methods: Consecutive patients who underwent clinically indicated CCTA and SPECT myocardial imaging for suspected CAD were included. Stenosis severity and segment involvement score (SIS - number of segments with plaque irrespective of stenosis) were determined from CCTA, and presence of ischemia was determined from SPECT. Patients were followed for major adverse cardiovascular events (MACE, inclusive of all-cause death, non-fatal myocardial infarction, and percutaneous coronary intervention or coronary artery bypass grafting 90-days after imaging test.) Results: A total of 956 patients were included (mean age 61.1 ± 14.2 years, 54% men, 89% hypertension, 81% diabetes, 84% dyslipidemia). Obstructive stenosis (left main ≥50%, all other coronary segments ≥70%) and ischemia were observed in a similar number of patients (14%). In multivariable Cox regression models, SIS significantly predicted outcomes and improved risk discrimination in models with CCTA obstructive stenosis (HR 1.15, p ≤ 0.001; Harrel's C 0.74, p = 0.008) and SPECT ischemia (HR 1.14, p < 0.001; Harrel's C 0.76, p = 0.019). Conclusions: Our results suggest that in patients with suspected CAD and a high prevalence of risk-factors, plaque burden adds incremental prognostic value over established CCTA and SPECT measures to predict incident cardiovascular outcomes. Graphical abstract: Image 1 Highlights: CCTA and SPECT are established tests in the evaluation of patients with suspected CAD. The burden of CAD has been recognized as an important determinant of patients' outcomes. We looked at consecutive patients with suspected CAD who had both CCTA and SPECT. We found plaque burden adds incremental prognostic value over established measures.